Rolleforståelser i kulturminneforvaltningen - Indregard, Rønnaug; Strand, Roger (Tidsskrift for kulturforskning, 2007)
According to §1 of the Norwegian Cultural Heritage Act of 1978, cultural heritage must be protected as "scientific source material and as an enduring basis for the experience of present and future generations and for their self-awareness, enjoyment and activities." The article presents a case study of a minor conflict over the protection of an automatically protected site located within a Norwegian farmer's property in the vicinity of a museum. The study shows how not only different interests are at stake, but also how the actors differ in the perception of the site and in their relationship to the past. Applying the old contrast between history and tradition, we argue that archeological expertise in cultural heritage management might give a bias towards history and away from living tradition when sites are to be valuated and protected. In this respect, the management processes would benefit from interdisciplinary inputs and public participation in the broad sense, in which citizens are seen to hold relevant knowledge about the value of cultural heritage as a basis for self-awareness, enjoyment and activities.